Influence of Separation Techniques with Acid Solutions on the Composition of Eggshell Membrane - Torres-Mansilla, A.C.; Delgado-Mejia , E. (International Journal of Poultry Science, 2017)
Background and Objective: The eggshell membrane is a biomaterial widely used in multiple fields of science. In order to use this biomaterial, the membrane needs to be separated from the shell. This procedure can be easily done manually but it could be inefficient and time consuming. Opposite to that, the acid dissolution of the shell represents an easy and efficient technique to obtain eggshell membrane. Some of the common acids used in this procedure are: acetic acid, EDTA and HCl. However, there is not enough information on the effect that these acids could cause in the organic eggshell membrane, neither on how these methods could affect its properties as a biomaterial. The objective of this study was to compare the influence of separation techniques with acid solutions, using Fourier Transform Infrared Spectroscopy (FTIR). Methodology: Pieces of 0.5 g eggshell were immersed into acid solutions, with an acid mass equivalent to four times the stoichiometrically calculated to dissolve the shell mineral. Manually obtained eggshell membranes were used as control. Afterwards, all the membranes were removed, washed with deionized water dried at 37°C overnigth. The samples of dried membranes were analyzed with FTIR-KBr (potassium bromide) and ATR (Attenuated Total Reflection) sample preparation techniques. Results: The FTIR-KBr and ATR techniques revealed that the absorption bands, related to the organic structure of the eggshell membrane, were modified by the HCl and EDTA-Na2 solutions, while the CH3COOH produced minimal changes. Conclusion: The eggshell membrane separation technique with CH3COOH solution preserves the organic structure of the eggshell membrane. Among the other acid solutions, the CH3COOH solution might be suitable to separate the eggshell membrane more efficiently than manual separation, without producing changes in the chemical composition of its structure.